Culture, reproduction and embryogenesis of wild zebrafish (Danio rerio) in laboratory condition - Rabbane, Md Golam; Ahmed, Md Feroz; Alam, Mohammad Shamimul; Hossain, Md Motaher (Dhaka University Journal of Biological Sciences, 2016)
Zebrafish (Danio rerio: Hamilton, 1822) is a well-known model organism of biological research. Generally it is found in the fresh water ponds. However, the culture, breeding and embryonic development of wild D. rerio of Bangladesh is scarcely represented in the literature. Therefore, a laboratory experiment was conducted to study these aspects of local zebrafish. Water quality parameters for adult fish husbandry system were recorded. These were temperature (°C) 29.18 ± 1.53, pH 7.55 ± 0.144, TDS (ppm) 225 ± 11.136, (ORP) 48.93 ± 26.04, DO (ppm) 1.24 ± 0.591, conductivity (mS/cm) 0.450 ± 0.022, are resistivity (Mῼcm) 0.0026 ± 0.00049 for adult fish tanks. The parameters obtained from larvae rearing ranks were temperature (°C) 29.56 ± 0.777, pH 7.73 ± 0.421, TDS (ppm) 198.33 ± 39.627, (ORP) 51.37 ± 17.387, DO (ppm) 2.02 ± 0.694, conductivity (mS/cm) 0.397 ± 0.079, resistivity (MΩcm) 0.0026 ± 0.00044. After one month of rearing, adult male and female fishes were selected for natural breeding and spawning and obtained 87.5 ± 7.72% spawning success, 96.83±0.81% fertilization rate and 94.89 ± 0.27% hatching rate. The embryonic development for zygote, cleavage, blastula, gastrula, segmentation and pharyngula periods were observed and obtained proper development for each state at 28.5ºC. The survival rate of hatchlings was 10 - 20% up to 20 days post fertilization. The higher spawning success, fertilization rate, hatching rate and survival rate indicate the possibility and potentiality of culturing zebrafish in laboratory conditions and could be established as a model animal for Bangladeshi researchers. Dhaka Univ. J. Biol. Sci. 25(2): 139-148, 2016 (July)